2013
DOI: 10.1590/s0102-311x2013001200010
|View full text |Cite
|
Sign up to set email alerts
|

Disparidades étnico-raciais em saúde autoavaliada: análise multinível de 2.697 indivíduos residentes em 145 municípios brasileiros

Abstract: (OR = 1.71; 95%CI: 1.24; 2.37 and OR = 1.37; 95%CI: 1.10; 1.71, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…Given the homogeneity of the variables representative of the socioeconomic level in the study area and that the non-whites were almost exclusively black and mixed individuals in our study, the fact they showed increased odds for seropositivity for dengue may be a reflection of the worse socioeconomic status of these people in Brazil. A study carried out in Brazil showed that black and mixed-race people presented a higher odds of a negative self-rated health than whites even after controlling for socioeconomic and demographic covariates [65].…”
Section: Discussionmentioning
confidence: 99%
“…Given the homogeneity of the variables representative of the socioeconomic level in the study area and that the non-whites were almost exclusively black and mixed individuals in our study, the fact they showed increased odds for seropositivity for dengue may be a reflection of the worse socioeconomic status of these people in Brazil. A study carried out in Brazil showed that black and mixed-race people presented a higher odds of a negative self-rated health than whites even after controlling for socioeconomic and demographic covariates [65].…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is a public health problem that is directly related to poverty and has been associated with low body mass index 10 . This could be due to more precarious living conditions, which include lower incomes and more limited access to health services, a common reality among the Brazilian black and "pardo" population 11 . In Brazil, the "mixed" ethnic category is called "pardo", which means a mixture of European, black, and Amerindian 12 .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies cite that being of non‐white color is a predictive factor for increased risk of high arterial blood pressure, 70 vitamin D deficiency, and a higher risk for the development of GDM 71 . Still, other studies have shown that social inequalities where skin color is differentiated persist, imposing unfavorable socioeconomic conditions on non‐white people, and this condition is still an aggregator of social inequalities, especially in middle‐income countries 72–74 . Since non‐white color/ethnicity was relevant both for the individual outcome and in the analysis that associated all the summed outcomes, it was decided to maintain this variable in the proposal for a framework.…”
Section: Discussionmentioning
confidence: 99%
“…socioeconomic conditions on non-white people, and this condition is still an aggregator of social inequalities, especially in middleincome countries. [72][73][74] Since non-white color/ethnicity was relevant both for the individual outcome and in the analysis that associated all the summed outcomes, it was decided to maintain this variable in the proposal for a framework. Concerning education or illiteracy, although education failed to have a relevant result in the present study, women were not differentiated by literacy but by years of education.…”
Section: Discussionmentioning
confidence: 99%